PENGETAHUAN DAN PERILAKU PENCEGAHAN LUKA KAKI DIABETIK - Imron Prasojo, Dudy; Pratama, Kharisma; Rahmawati, Annisa (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Diabetes mellitus (DM) is a chronic disease caused by the pancreas' inability to produce or use insulin effectively, typically characterized by hyperglycemia. Hyperglycemia increases the risk of diabetic foot ulcers. Prevention of diabetic foot ulcers heavily relies on proper foot care practices, which are influenced by the patient's level of knowledge. Insufficient knowledge can lead to suboptimal preventive behaviors, thereby increasing the risk of complications. Objective: This study aims to investigate the relationship between knowledge levels and preventive behaviors regarding the occurrence of diabetic foot ulcers among patients with type II diabetes mellitus at the 'Aisyiyah Singkawang Clinic. Methods: This study used a quantitative approach with a cross-sectional design. Cluster sampling was used to select 192 respondents. The research instrument consisted of a questionnaire to measure knowledge levels and preventive behaviors. Data analysis was performed using the chi-square statistical test. Results: A p-value of <0.05 was obtained, indicating a significant association between knowledge levels and preventive behavior regarding diabetic foot ulcers among diabetes mellitus patients at the ‘Aisyiyah Singkawang Clinic. Conclusion: The higher the patients’ knowledge levels, the better their preventive behavior regarding diabetic foot ulcers. Therefore, education and health counseling are essential.